Hollywood ending - Aronson, Letty, 1943-; Allen, Woody, 1935-; Hamilton, George, 1939-; d ct; Messing, Debra, 1968-; Rydell, Mark, 1934-; Williams, Treat; Von Schultzendorff, Wedigo; Kepselter, Alisa; Toth, Melissa; Loquasto, Santo; DreamWorks Pictures (1994-2006); et al. ([United States] : DreamWorks Home Entertainment, 2002)
Val Waxman is a one-time cinematic genius down on his luck. Luckily, he receives a script for a period noir set against the backdrop of 1940s New York City. His ex-wife has managed to convince a high-powered studio head, to take a chance on Val's "unique vision." Just when the cameras are ready to roll, however, Val finds that unique vision in jeopardy -- literally -- as he's struck with a psychosomatic case of blindness. When efforts to cure him fail, Val contrives a scheme to forge ahead with the picture, for fear of blowing his one last chance at greatness.
Also available in box set: Woody Allen four-movie comedy collection.
Special features: production notes; theatrical trailer; cast & crew bios.
Director of photography, Wedigo von Schultzendorff ; editor, Alisa Lepselter ; costume designer, Melissa Toth ; production designer, Santo Loquasto.
Woody Allen, George Hamilton, Tea Leoni, Debra Messing, Mark Rydell, Treat Williams.
MPAA rating: PG-13; for some drug references and sexual material.
Also issued on VHS.
Keywords: Motion picture producers and directors -- Drama; Motion picture industry; Closed captioning; Producers and directors; Feature films -- United States; Comedy films; DVD-Video discs; Fiction films; Video recordings for the hearing impaired